Improving the anti-oxidation of glucose oxidase with computer-aided structure optimization - Jiang, Zheng-Bing; Song, Hui-Ting; Xiao, Wen-Jing; Yang, Yi-Min; Zhao, Yong; Gao, Yuan; Liu, Shi-Hui; Liu, Zi-Lu; Xia, Wu-Cheng; Li, Rong; Li, Nuo-Nan (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Glucose oxidase (GOD) can be inactivated by hydrogen peroxide (H2O2) produced during glucose oxidation; thus, H2O2 is a competitive inhibitor of GOD. In this mechanism, methionine (Met), a sulfur-containing amino acid, can be oxidized by H2O2and converted into methionine sulfoxide, thereby inactivating GOD. In this study, to block GOD oxidation, the two-dimensional structures of three mutants were designed with computer-aided analysis, and the complex structures of GOD mutants and their substrate glucose were determined using the CDOCKER algorithm. Three mutant GODs and the wild-type GOD were expressed in Pichia pastoris. After purification, the activities and anti-oxidation capacities were evaluated. The activity of GOD was decreased substantially from 3.24 U/Î¼g in the wild-type protein to 0.05 U/Î¼g in the GOD-M523L-M524L mutant; in contrast, the activity of GOD-M524L-M528L was not different from that of the wild-type protein. Because the activity of GOD-M523L-M524L was negligible, we did not evaluate its anti-oxidative effects. However, the mutant GOD-M524L-M528L had better anti-oxidation capacity than the wild-type GOD. These results were consistent with the results of computer-aided analysis, suggesting that this method may be useful for enzyme structure optimization.